The study of the copper vapor brightness amplifier for longdisplacement objects visualization; Proceedings of SPIE; Vol. 10614 : XIII International Conference on Atomic and Molecular Pulsed Lasers - Vlasov V. V. Vasily Vasiljevich (2018, 2018)
Title screen